(untitled) (Academia Science Repository, 2023)
The immunomodulatory effect of the autonomic nervous system has gained significant interest in recent decades. Studying the influenc e on the immune system and the roles in inflammation of both sympathetic and parasympathetic nervous systems not only expands our understanding of the disease mechanism, but also may lead to the discovery of potential new therapeutic targets in chronic imm une mediated inflammatory diseases, such as rheumatoid arthritis (RA). An imbalanced